CFD simulation of porous microsphere particles in the airways of pulmonary fibrosis. (October 2022) - Qin, Zhilong; Shi, Yanbin; Qiao, Jinwei; Lin, Guimei; Tang, Bingtao; Li, Xuelin; Zhang, Jing
Highlights: Pulmonary fibrosis makes it more difficult for microspheres to enter subsequent airways. There is a significant difference between the deposition patterns of mice and humans. Porous microspheres can significantly improve the bronchial deposition of larger microspheres. It is necessary to establish a specific respiratory tract model for pulmonary fibrosis to study particle deposition. Abstract: Background and objective: Pulmonary fibrosis (PF) is a chronic progressive disease with an extremely high mortality rate and is a complication of COVID-19. Inhalable microspheres have been increasingly used in the treatment of lung diseases such as PF in recent years. Compared to the direct inhalation of drugs, a larger particle size is required to ensure the sustained release of microspheres. However, the clinical symptoms of PF may lead to the easier deposition of microspheres in the upper respiratory tract. Therefore, it is necessary to understand the effects of PF on the deposition of microspheres in the respiratory tract. Methods: In this study, airway models with different degrees of PF in humans and mice were established, and the transport and deposition of microspheres in the airway were simulated using computational fluid dynamics. Results: The simulation results showed that PF increases microsphere deposition in the upper respiratory tract and decreases bronchial deposition in both humans and mice. Porous microspheres with low density can ensure deposition in the lower respiratory tract and larger particle size. In healthy and PF humans, porous microspheres of 10 µm with densities of 700 and 400 kg/m³ were deposited most in the bronchi. Unlike in humans, microspheres larger than 4 µm are completely deposited in the upper respiratory tract of mice owing to their high inhalation velocity. For healthy and PF mice, microspheres of 6 µm with densities of and 100 kg/m³ are recommended. Conclusions: The results showed that with the exacerbation of PF, it is more difficult for microsphere particles to deposit in the subsequent airway. In addition, there were significant differences in the deposition patterns among the different species. Therefore, it is necessary to process specific microspheres from different individuals. Our study can guide the processing of microspheres and achieve differentiated drug delivery in different subjects to maximize therapeutic effects.